Strengthening Regulations for Supervision of Private Sector Grant Funds in View of Law no. 17 of 2003 concerning State Finances - Evangelista, Beverly; Setiawan, Muhammad Rifaldi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research discusses the importance of strengthening regulatory oversight of grant funds in the private sector to prevent misuse and increase accountability. The background to the problem includes the increasing allocation of grant funds to private institutions and current challenges in supervision. The method used in this discussion includes normative analysis of Law no. 17 of 2003 as well as case studies that show weaknesses in existing supervision and sanctions. The results of the analysis show that regulatory revisions are needed to establish stricter audit standards, increase reporting obligations, and strengthen legal sanctions for violators. The conclusion of this research confirms that by strengthening regulations, it is hoped that the management of grant funds by private institutions can be carried out in a more transparent and accountable manner, thereby increasing public trust in the use of these funds.